Design and demonstration of a tri‐band frequency selective surface for space applications in X, K, and Ka bands. Issue 4 (9th January 2020) - Abdollahvand, Mousa; Forooraghi, Keyvan; Encinar, Jose A.; Atlasbaf, Zahra; Martinez‐de‐Rioja, Eduardo
Abstract: A novel tri‐band frequency selective surface (FSS) is proposed for space antenna systems in the X, K, and Ka bands. The FSS structure is based on a two‐layer configuration, where the unit‐cell elements at each layer consist of two pairs of rectangular‐shaped dipoles and a square ring. The FSS has been designed to be transmissive at 11.5 GHz (X band) and totally reflective at 20 GHz (K band) and 30 GHz (Ka band). The reflection losses in K and Ka bands are less than 0.1 dB for incidence angles varying from 0° to 45°. Also, the transmission losses in X band are less than 0.5 dB for incidence angles of up to 30°. A 30‐cm prototype of the proposed two‐layer FSS has been fabricated and tested. Both simulation and measurement results show a good agreement and a satisfactory performance in the three operating bands.